2019
DOI: 10.1101/822320
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Crowdsourcing neuroscience: inter-brain coupling during face-to-face interactions outside the laboratory

Abstract: When we feel connected or engaged during social behavior, are our brains in fact "in sync" in a formal, quantifiable sense? Most studies addressing this question use highly controlled tasks with homogenous subject pools. In an effort to take a more naturalistic approach, we collaborated with art institutions to crowd-source neuroscience data: Over the course of 5 years, we collected electroencephalogram (EEG) data from thousands of museum and festival visitors who volunteered to engage in a 10-minute face-to-f… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3
3

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 78 publications
0
14
0
Order By: Relevance
“…Indeed, some have suggested that joint attention to stimulus features during processing of naturalistic stimuli may underlie coupled neural responses Dikker et al, 2019). Decreased Teacher-Student Unscrambled coupling in high-level regions, including DMN, may thus reflect lower attention rather than disrupted learning.…”
Section: Limitations and Future Directionsmentioning
confidence: 99%
“…Indeed, some have suggested that joint attention to stimulus features during processing of naturalistic stimuli may underlie coupled neural responses Dikker et al, 2019). Decreased Teacher-Student Unscrambled coupling in high-level regions, including DMN, may thus reflect lower attention rather than disrupted learning.…”
Section: Limitations and Future Directionsmentioning
confidence: 99%
“…Additionally, EEG hyperscanning has demonstrated interpersonal synchrony when people are performing coordinated movements (22)(23)(24)(25)(26). Importantly, correlations between participants' EEG activity may be shaped by a host of individual differences, including empathy, social closeness, and autistic traits (27,28). Clinically, hyperscanning approaches may also be especially relevant to our understanding of the neural basis of autism (12).…”
Section: Introductionmentioning
confidence: 99%
“…This study was conducted as part of the participatory art installation Mutual Wave Machine, a Brain-Computer Interface (BCI) that translates real-time correlation of pairs’ EEG activity into light patterns (described in detail in Dikker et al, 2021; also see wp.nyu.edu/mutualwavemachine). This setup allowed us to study real-world face-to-face social interactions in a large population of participants recruited outside of the traditional research subject pool.…”
Section: Methodsmentioning
confidence: 99%
“…Using a range of metrics to quantify inter-brain connectivity (Ayrolles et al, 2021), inter-brain coupling has been linked to a variety of factors during both verbal and non-verbal social tasks (Czeszumski et al, 2020). During social interactions outside of laboratory environments, our group has previously found that inter-brain coupling is linked to social closeness, personal distress, and shared social attention (Dikker et al, 2017, 2021).…”
Section: Introductionmentioning
confidence: 99%